Engagement Strategies for Stakeholder Management in New Technology Development in the Fertilizer Industry – A Conceptual Framework - Ammar Redza, Ahmad Rizal; Shahrina, Md Nordin; Mohd Shamsuri, Saad; Kamariah, Ismail (World Academy of Science, Engineering and Technology, 2012)
Communication is becoming a significant tool to engage stakeholders since half of the century ago. In the recent years, there has been rapid growth of new technology developments. In tandem with such developments, there has been growing emphasis in communication strategies and management especially in determining the level of influence and management strategies among the said stakeholders on particular field. This paper presents a research conceptual framework focusing on stakeholder theories, communication and management strategies to be implied on the engagement of stakeholders of new technology developments of fertilizer industry in Malaysia. Framework espoused in this paper will provide insights into the various stakeholder theories and engagement strategies from different principal necessary for a successful introduction of new technology development in the above stated industry. The proposed framework has theoretical significance in filling the gap of the body of knowledge in the implementation of communication strategies in Malaysian fertilizer industry.